factorise this question and tell me the answer fast
Attachments:
![](https://hi-static.z-dn.net/files/d7c/8b77ad67261abc76d3b2c1d98bf05d4d.jpg)
Answers
Answered by
1
125x^3+y^3
=(5x)^3+(y)^3
using identity a^3+b^3=(a+b)(a^2-2ab+b^2)
=(5x+y)(25x^2-5xy+y^3)
=(5x)^3+(y)^3
using identity a^3+b^3=(a+b)(a^2-2ab+b^2)
=(5x+y)(25x^2-5xy+y^3)
Answered by
2
given that,
![125 {x}^{3} + {y}^{3} 125 {x}^{3} + {y}^{3}](https://tex.z-dn.net/?f=125+%7Bx%7D%5E%7B3%7D++%2B++%7By%7D%5E%7B3%7D+)
=(5x)^3+y^3
this is in the form of
(a^3+b^3)=(a+b)(a^2+b^2-ab)
=(5x+y)((5x)^2+y^2-5x*y)
=(5x+y)(25x^2+y^2-5xy)
pls mark as brainliest.
=(5x)^3+y^3
this is in the form of
(a^3+b^3)=(a+b)(a^2+b^2-ab)
=(5x+y)((5x)^2+y^2-5x*y)
=(5x+y)(25x^2+y^2-5xy)
pls mark as brainliest.
Similar questions